Toxicity of copper nanoparticles and CuCl2 salt to Enchytraeus albidus worms: survival, reproduction and avoidance responses - Amorim, Mónica João Barros (2019)
Environmental effects of copper nanoparticles are little studied in terrestrial ecosystems. In the present article, the toxicity of copper nanoparticles (Cu-NP) on the enchytraeid Enchytraeus albidus is compared to the toxicity of a copper-salt (CuCl(2)). The effect parameters studied were survival, reproductive output and avoidance behaviour. The results show that Cu-NP were more toxic to E. albidus than the same concentrations of the CuCl(2)-salt. The physic-chemical analysis of the particles indicated that only a small fraction was released as ions. Hence, the results indicated a nanoparticle-specific effect - lower reproductive output and higher avoidance. This was observed as 2-8 fold (significant) lower ECx values for Cu-NP (EC(50-reprod) = 95 mg Cu/kg; EC(50-avoid) = 241 mg Cu/kg) exposed organisms compared to CuCl(2) (EC(50)(-)(reprod) = 251 mg Cu/kg; EC(50-avoid) = 475 mg Cu/kg) exposed organisms. These results corroborate with a nanoparticle-specific effect.